A Delphi study on research priories in radiation therapy: the Australian perspective - Cox, J.; Halkett, Georgia; Anderson, C.; Heard, R. (Elsevier Ltd, 2009)
Radiation therapists (RTs) need to engage more in research to establish an evidence base for their daily practice. However, RTs world-wide conduct little research themselves, although positive moves have been made in some countries. This project is the second stage of a Delphi process aimed at prioritising RT areas of research interest. A questionnaire was constructed using responses to a previous questionnaire which identified the research interests of Australian RTs. Fifty-three Research Areas were identified from these responses and grouped into 12 categories such as “imaging in radiation therapy”, “symptom management”, “accuracy of patient positioning” and “techniques/equipment”. The survey was sent to all Australian departments of radiation oncology, and RTs were asked to form interest groups to discuss and prioritise the Research Areas. There was a 50% response rate (18 of 36 departments surveyed). The highest ranked research Category was “imaging in radiation therapy”. Six of the top 10 ranked Research Areas were within Central RT practice (“imaging in radiation therapy”; “symptom management”; “accuracy of patient positioning” and “techniques/equipment”) and the other four were within broader RT practice (“diversification, recognition and other professional issues”; and “management and staff issues”). Patient Care was also considered to be an area requiring more research. This prioritization of Research Areas and categories provides a useful list of future research for RTs, which will enable them to decide whether their research ideas are a high priority, and spend less time deciding on a relevant research topic that needs investigation in their own workplaces.